Pengaruh Nisbah Energi-Protein, Nitrogen-Sulfur dan Kalsium-Fosfor Terhadap Produk Metabolisme Rumen dan Kecernaan Substrat - S.N.O. Suwandyastuti (Agricultural Faculty, 2013)
Influence of the ratio of energy-protein, nitrogen-sulphur, and calsium-phosphor upon rumen metabolism product and digestibility of substratABSTRACT. The Rumen microbes are capable to digest the glucosa polymer of plant waste for energy source and can used the Non Protein Nitrogen (NPN) for body protein synthesis, if the other precussor (Sulphur, Phospor and Branch Chain of Carbon) are available. To know the effectivity of the utilization of plant waste for energy, an experiment have been conducted by in vitro method, used the Randomized Black Design, four replication, factorial 33. The factors tested are : (1) three levels of energy : protein (E/P) ratio : 4, 5 and 6; (2) three levels of Nitrogen : Sulphur (N/S)ratio: 7.5, 10 and 12.5; (3) three levels of Calsium : Phospor (Ca/P) ratio : 0.5, 1 and 2. The variables measured are : synthesis of protein microbes (SPM) ; production of Volatile Fatty Acid (VFA) and Nitrogen Ammonia (N-NH3); the digestibility of substrat. Based on the all variable measured, the experiment can be concluded : (1) the effectivity of the utilization of rice straw will be increased if it used is fortified with 50 percent TDN as energy source (E/P=4), 0.20 percent dry matter of sulphur (N/S=10) and 0.0625 - 0.125 percent dry matter (DM) of phospor (Ca/P=1.0 2.0); (2) To stimulate the activity of cellulolytic microbes, its need the fortification of sulphur until reach the optimum level (must be investigated).